Pengaruh Kemajuan Digital Terhadap Perubahan Media Investasi Gen Z Pada Mahasiswa UMBY - Dani Permana; Maria Chandrayani Bai Nai; M.Rizky Ardi Saputra (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research uses a positivism paradigm and quantitative descriptive research methods using questionnaires. The target population of this research is regular morning students at Mercu Buana University, Yogyakarta. Samples will be taken using Slovin Formula This research aims to investigate how the development of digital technology and the internet has influenced the way Generation Z (students) use media for investment purposes. The main focus of the research is how to understand the shift in media preferences used by Generation Z in the context of investment, finance and how this is reflected in their behavior along with the development of digital technology, this research also includes an analysis of its impact on investment decisions, as well as the potential for changes in the investment paradigm of generation z in the context of higher education, the sample collection method uses a probability sampling technique using a simple random sample. random sampling) research variables consist of independent variables (digital progress) and dependent variables (changes in investment media)